2016
DOI: 10.3892/mmr.2016.4880
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations in inflamed and unaffected colon mucosa from patients with mild inflammatory bowel disease

Abstract: Abstract. An endoscopic examination is currently the most reliable method for monitoring disease activity in patients with inflammatory bowel disease (IBD). However, endoscopic evaluations are unable to detect mucosal inflammation at the earliest stages. The present study aimed to evaluate the molecular profiles of inflamed and unaffected colon mucosa from patients with mild Crohn's disease (CD) and ulcerative colitis (UC), in order to identify a more sensitive method for monitoring mucosal impairment. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
1
6
0
1
Order By: Relevance
“…Various transcriptomic studies have been carried out in the IBD field, including several efforts to discriminate between disease subtypes [Crohn’s disease vs UC], disease phase [active/mildly active/inactive], 7,8 colon biopsy locations, 9 genders, 10 etc. Some of these studies have also been previously reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Various transcriptomic studies have been carried out in the IBD field, including several efforts to discriminate between disease subtypes [Crohn’s disease vs UC], disease phase [active/mildly active/inactive], 7,8 colon biopsy locations, 9 genders, 10 etc. Some of these studies have also been previously reviewed.…”
Section: Introductionmentioning
confidence: 99%
“… 17 34 35 In transcriptomic studies of IBD, most of the aberrant mRNAs were found to be involved in molecular functions associated with immune response, mucosal inflammation, nutrients absorption, epithelial damage, oncogenesis and cell proliferation. 21 36 37 …”
Section: Different Types Of Rnas and Their Associations With Diseasesmentioning
confidence: 99%
“…They discovered that several genes were deregulated in the inactive UC despite histological recovery [ 5 ]. Another microarray study demonstrated that expression of INF‑γ and IL‑17 was comparably elevated in both inflamed and unaffected colon mucosa from patients with IBD, indicating that the inflammatory response is not limited to the endoscopic lesions [ 6 ]. Smith et al identified that dysregulation of BMP/retinoic acid inducible neural specific 3 plays a role in the pathogenesis of UC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%